MODEL KURIKULUM SD, MI, SMP, DAN MTS, DAN PERBEDAAN KURIKULUMNYA (SECARA SPESIFIK) - Mesi Mesi (Al-SAMBASY: Jurnal Kajian Pendidikan, 2024)
The curriculum in education serves as the foundation for the learning process at the elementary, middle, and secondary levels. This article explores the curriculum models used in Primary Schools (SD), Islamic Primary Schools (MI), Junior High Schools (SMP), and Islamic Junior High Schools (MTs), along with the diflerences between them. Through literature review and comparative analysis, this article identifies the approaches, structures, and learning focuses of each curriculum model. Understanding these diflerences allows for an appreciation of diversity in education and evaluation of the strengths and challenges associated with each curriculum model.